2013
DOI: 10.1001/jamasurg.2013.1341
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injuries in Developing Countries

Abstract: Objective Despite the tremendous disability and mortality caused by traumatic injuries worldwide, there is a relative dearth of information on the burden of injuries in developing countries. In an effort to document the surgical burden of disease in Sierra Leone, a nationwide survey was conducted utilizing the Surgeons OverSeas Assessment of Surgical Need (SOSAS) tool. Here, we report the injury data from this study with the aim to (1) provide an estimate of injury prevalence, (2) determine the mechanisms of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 23 publications
7
38
0
1
Order By: Relevance
“…Sierra Leone is a country situated on the West coast of Africa with a population of just over 7 million people. It is amongst the world’s poorest countries, ranked 179 out of 188 countries in the Human Development Index with a life expectancy of 53 years [8] with injury representing 7% of the burden of disease [9] and responsible for an estimated 325,000 deaths [10] . It is currently recovering from the worst Ebola epidemic on record during which 221 health care workers lost their lives [11] and medical and surgical services were severely disrupted across the country, including at the only adult tertiary referral centre [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Sierra Leone is a country situated on the West coast of Africa with a population of just over 7 million people. It is amongst the world’s poorest countries, ranked 179 out of 188 countries in the Human Development Index with a life expectancy of 53 years [8] with injury representing 7% of the burden of disease [9] and responsible for an estimated 325,000 deaths [10] . It is currently recovering from the worst Ebola epidemic on record during which 221 health care workers lost their lives [11] and medical and surgical services were severely disrupted across the country, including at the only adult tertiary referral centre [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it had been reported that road traffic injuries was the major source of injuries in patients presenting to the hospitals of some African countries such as Uganda, Ghana, and Tanzania ( 11 ). However, in another study from Sierra Leone, a mid-income West African country, fall, lacerations, and crush injuries were the first and second most common causes of injury, respectively ( 12 ). On the other hand, falls are among the life events that lead to injury and in serious cases disability or death ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 While falls are common in LMICs, such a high incidence of fall injuries is not usually reported during peacetime (447 per 100,000 persons in 2013). 4, 14, 22 For comparison, the reported rate of serious fall injuries from other Middle Eastern countries that have not been affected by recent conflict (e.g. United Arab Emirates, Iran, Qatar) ranges from 64 – 237 per 100,000 persons, even among high-risk groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…7, 14, 15 A survey instrument was adapted from the World Health Organization's community injury survey guidelines and the Surgeons OverSeas Assessment of Surgical Need (SOSAS). 14-16 The instrument was translated into Arabic, back translated to assure accuracy and piloted for utility and validity. The final version was designated the Surgeons OverSeas Injury Survey (SOSINJ).…”
Section: Methodsmentioning
confidence: 99%